2014
DOI: 10.5171/2014.506946
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Flow Rate, pH and Buffering Capacity in Pregnant and Non Pregnant Women - A Comparative Study

Abstract: The objective of this article is to evaluate salivary flow rate, pH and buffering capacity of saliva in pregnant and non pregnant women. The present study was a comparison between 30 pregnant women in their third trimester and 30 non pregnant women, in the age group of 19-34 years. The salivary flow, pH, and buffering capacity was measured using Saliva-check BUFFER kit (GC Corporation). Both unstimulated and paraffin stimulated saliva was measured for 5 min by asking the subjects to spit passively into a measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
1
19
0
8
Order By: Relevance
“…Hence, it plays a major role in maintenance of oral health. 8 Present study revealed that the salivary flow rate and pH of saliva decreased in pregnant women than in non-pregnant women. Similar results has also been obtained by Rockenbach M, et al 9 who did a cross sectional study in 2006 to compare the salivary flow rate, pH on 22 pregnant and non-pregnant women in Obstertics and Gyneocology clinics in Sao Lucas Hospital in Brazil.…”
Section: Resultsmentioning
confidence: 47%
“…Hence, it plays a major role in maintenance of oral health. 8 Present study revealed that the salivary flow rate and pH of saliva decreased in pregnant women than in non-pregnant women. Similar results has also been obtained by Rockenbach M, et al 9 who did a cross sectional study in 2006 to compare the salivary flow rate, pH on 22 pregnant and non-pregnant women in Obstertics and Gyneocology clinics in Sao Lucas Hospital in Brazil.…”
Section: Resultsmentioning
confidence: 47%
“…6,12,13,15,[19][20][21][22][23][24] Among all the analysis performed, and taking together previous studies and the present study, we can confidently assume that pregnancy reduces non-stimulated saliva pH. 6,12,13,19,21 The decrease of saliva pH during pregnancy may be partially justified by the higher number of daily meals. 6,26 The acidic saliva throughout pregnancy represents a risk factor for dental caries development.…”
Section: ■ Discussionmentioning
confidence: 61%
“…14,15,21,23,34,35 Regarding salivary flow rate, most studies, including ours, reported no changes between pregnant and nonpregnant women; 6,13,19,20 however, Naveen et al 12 showed higher rates for either stimulated or non-stimulated saliva. In addition, reports regarding salivary flow rate throughout pregnancy are controversial, 34,35 suggesting that many factors may regulate this flow during pregnancy.…”
Section: 1931-33mentioning
confidence: 61%
See 1 more Smart Citation
“…It is believed that it occurs as an accompaniment of nausea during the first trimester as a result of increase in the levels of estrogen and progesterone. 23,24 Although, this raises the question as to why sialorrhoea is not expressed in as many pregnancies as nausea.…”
Section: Discussionmentioning
confidence: 99%